2008
DOI: 10.1159/000168009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Insect Phenoloxidase after Injury: Endogenous versus Foreign Elicitors

Abstract: The enzyme phenoloxidase (PO) is one of the first immune molecules that was identified in invertebrates. Recently, the immune function of PO has been challenged. We tested how PO is activated following injury in 2 insects, i.e. the fruit fly Drosophila melanogaster and the wax moth Galleria mellonella. Rapid PO activation in Drosophila was limited to discrete areas of the hemolymph clot which forms after injury. Surprisingly, unlike systemic PO activation during bacterial sepsis, clot melanization was not sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 68 publications
6
86
0
1
Order By: Relevance
“…These results unequivocally demonstrate the ability of various coral species to induce melaninsynthesis pathway activity in the presence of pathogen elicitors, as documented for numerous other invertebrates (e.g. Asokan et al, 1997;Bidla et al, 2008;Xian et al, 2009). Consistent with the findings for S. intersepta and P. astreoides, invertebrates induce PPO activity during the invasion of foreign organisms, as the cytotoxic properties of the melanin-synthesis pathway aid in the elimination of pathogens (Nappi and Ottaviani, 2000).…”
Section: Melanin-synthesis Pathwaysupporting
confidence: 72%
“…These results unequivocally demonstrate the ability of various coral species to induce melaninsynthesis pathway activity in the presence of pathogen elicitors, as documented for numerous other invertebrates (e.g. Asokan et al, 1997;Bidla et al, 2008;Xian et al, 2009). Consistent with the findings for S. intersepta and P. astreoides, invertebrates induce PPO activity during the invasion of foreign organisms, as the cytotoxic properties of the melanin-synthesis pathway aid in the elimination of pathogens (Nappi and Ottaviani, 2000).…”
Section: Melanin-synthesis Pathwaysupporting
confidence: 72%
“…Mono-phenoloxidase activity, the precursor to both tyrosinase-type and laccase pathways ( figure 1; [12]), was present in all species and varied the least among them. However, activities of the tyrosinase-type and laccase POs and PPOs varied significantly among taxa, indicating functional differences of these pathways [13,23]. For the majority of species, tyrosinase-type activity (o-diphenol substrates) was the highest of the three POs and PPOs, indicating greater baseline activity of this pathway than laccase.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of correlation with tyramine and the o-diphenols suggests that the tyrosinase-type pathway is not dependent upon mono-phenoloxidase for activation. As the tyrosinase-type melanin-synthesis pathway is highly cytotoxic and probably involved more specifically in immune defence [3,23], rather than clot stabilization or maintenance [15], it may have tighter controls on activation and different triggers [26] to the laccase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…all ProPO and all PO activity), nor the singular PO activity response. It has been shown that some ProPO is spontaneously activated during the process of haemolymph extraction (Bidla et al, 2009), and it may be this by-product that is being measured in the PO activity assay. Whilst we cannot rule out the fact that such activation has occurred, we would expect these measures to be uniform across all individuals studied when subject to the same collection protocols.…”
Section: Discussionmentioning
confidence: 99%
“…data), with a Michaelis constant (Km) of 5.75 mM, giving an optimal reaction velocity (Vmax, equal to 2 × Km) with 11.5 mM L-dopa (data not shown). Although solubilities as high as 10 or 20 mM have been recorded (Sinsabaugh et al, 1991;Bidla et al, 2009), L-dopa is considered sparingly soluble in water, making the Vmax calculated for honey bees unlikely to be easily achievable (Merck Index, 2006). To establish a workable concentration of L-dopa to yield maximum possible results, L-dopa solutions were tested using the Km (5.75 mM; after 10 min vortexing the solution reached saturation at this point and failed to dissolve further to provide the concentration needed for 2 km (V max )) and half Km (2.88 mM) concentrations in distilled water.…”
Section: Evaluating Kmmentioning
confidence: 99%